Effect of Early Post-Hatch Feeding on Immunity of Commercial Broilers - Desai, Dharmik M; Vahora, Safi G; Patel, Minnat M; Pathan, Mohsinkhan M; Panchal, Dhrumil K (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Early feeding plays a crucial role in the rapid growth and immune system development of newly hatched chicks, improving their disease resistance significantly. A total of 144 day-old chicks were randomly assigned to four treatment groups, each consisting of 9 birds per replicate and 4 replicates per group. In the control group, chicks were provided with water and pre-starter feed immediately upon their arrival at the farm from the commercial hatchery. In the T1 group, feed and water were supplied 12 h after arrival, while in the T2 group, they were offered 24 h post-arrival. In the T3 group, feed and water were made available immediately after hatching on the farm. The average log10 values of HI antibody titers, along with the mean percentages of heterophils, lymphocytes, monocytes, eosinophils, and basophils, did not show statistically significant differences in blood samples collected on days 7, 21, and 42 across the Control, T1, T2 and T3 groups. Similarly, the results of the haematological analysis, including differential leukocyte counts, indicated no significant variations among the four groups. Histo-morphological examination of the spleen, thymus, and bursa of Fabricius revealed a normal tissue structure on days 7, 21, and 42 across all experimental groups.